Highly Effective Renaturation of a Streptokinase from Streptococcus pyogenes DT7 as Inclusion Bodies Overexpressed in Escherichia coli. (5th May 2014) - Nguyen, Sy Le Thanh; Quyen, Dinh Thi; Vu, Hong Diep
Abstract : The streptokinase (SK) is emerging as an important thrombolytic therapy agent in the treatment of patients suffering from cardiovascular diseases. We reported highly effective renaturation of a SK from S. pyogeness DT7 overexpressed in E. coli, purification, and biochemical characterization. A gene coding for the SK was cloned from S. pyogeness DT7. Because accumulation of active SK is toxic to the host cells, we have expressed it in the form of inclusion bodies. The mature protein was overexpressed in E. coli BL21 DE3/pESK under the control of the strong promoter tac induced by IPTG with a level of 60% of the total cell proteins. The activity of the rSK, renatured in phosphate buffer supplemented with Triton X-100 and glycerol, was covered with up to 41 folds of its initial activity. The purified of protein was identified with MALDI-TOF mass spectrometry through four peptide fragments, which showed 100% identification to the corresponding peptides of the putative SK from GenBank. Due to overexpression and highly effective renaturation of large amounts of inclusion bodies, the recombinant E. coli BL21 DE3/pESK system could be potentially applied for large-scale production of SK used in the therapy of acute myocardial infarction.